Follow the smoke: The pollution haven effect on global sourcing - Berry, Heather; Kaul, Aseem; Lee, Narae (Strategic Management Journal, 2021)
Abstract Research abstract We examine whether and how foreign environmental standards influence global sourcing decisions. Taking a question‐driven approach, we find a negative association between the stringency of a country's environmental standards and its share in US imports for 82 manufacturing industries across 77 countries between 2006 and 2016. This pollution haven effect holds not only for sourcing from owned foreign operations (offshore integration), but also for sourcing from unrelated third parties abroad (offshore outsourcing), and is stronger in industries with high toxic emissions and low technological intensity. These results are robust across alternative measures of environmental stringency and to using the Kyoto Agreement as an instrumental variable. These findings shed new light on how firms use global sourcing, and especially offshore outsourcing, to arbitrage across institutional environments. Managerial summary Prior work has shown that multinational firms prefer to locate their plants in countries with weak environmental standards: the so‐called Pollution Haven Effect. We extend this research to show that firms not only source from countries with weak environmental standards from their own plants, but also from third‐party foreign suppliers. Using Census data on US manufacturing imports from 77 countries between 2006 and 2016 we show that when the stringency of environmental standards in a country decreased, sourcing from that country increased, and that this effect was just as strong for sourcing from third parties as from owned operations. Our study thus suggests that previous work may have substantially underestimated the pollution haven effect, by focusing on owned global sourcing rather than all global sourcing.